Developing picture media to teach descriptive text at MAN 1 Blitar - Rumhin, Durin Alfia; Makrifah, Istina Atul; Saifudin, Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2023)
The purpose of this study is to know if students’ writing ability will increase after using picture media. In the English teaching and learning skill, the student still had a difficulty. The subject of the research was students on class X IPS 1 of MAN 1 Blitar. The participant of the research was 34 students of class X IPS 1. This research was categorized as Research and Development (R&D) by Borg and Gall. The steps of the research were research and information collecting, planning, develops preliminary of the product, preliminary field testing, main product revision, main field testing, and final product revision. The instruments used for collecting data were field note and questionnaire. The validity in this research were obtained through two judgment of expert, they were material expert and media expert. The result of this study categorized as valid with percentage of 90.27% material validation, 82.5% media validation, and 91.1% students’ response.